Applying the Data Center Infrastructure Management (DCIM) Tool to Enhance the Quality Management of the Data Centers by Decreasing the Unplanned Outage Reasons (International Journal of Innovative Research in Computer Science & Technology, 2022)
All previous reports and practical life have  proven that the human errors and devices failure are  responsible for the unplanned outage of the data centers at a  rate of up to 88%. And for this reason, it was important to  find a way to reduce this percentage. In this study, we discuss how the Data Center Infrastructure  Management system (DCIM) tool can reduce this  percentage and enhance the management quality that helps  to make most of the daily operations inside data centers run  routinely and easily. So, the main target of this case study is  finding that “if the Data Center Infrastructure Management  (DCIM) tool can help to reduce the main reasons of the  unplanned outage of the data centers and enhance the  quality management The information technology industry  consists of several stages, and one of the most important
Keywords: DCIM; Data Center; the quality management of the data centers; ISO 9001:2015 for data centers; data centers standards; and data centers management tools